Inhibitory effect of napabucasin on arbidol metabolism and its mechanism research - Jingjing Nie; Jingjing Nie; Hailun Xia; Ya-Nan Liu; Yige Yu; Ren-Ai Xu (Frontiers Media S.A., 2023)
As a broad-spectrum antiviral, and especially as a popular drug for treating coronavirus disease 2019 (COVID‐19) today, arbidol often involves drug-drug interactions (DDI) when treating critical patients. This study established a rapid and effective ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method to detect arbidol and its metabolite arbidol sulfoxide (M6-1) levels in vivo and in vitro. In this study, a 200 μL incubation system was used to study the inhibitory effect of the antitumor drug napabucasin on arbidol in vitro, with IC50 values of 2.25, 3.91, and 67.79 μM in rat liver microsomes (RLMs), human liver microsomes (HLMs), and CYP3A4.1, respectively. In addition, we found that the mechanism of inhibition was non-competitive inhibition in RLM and mixed inhibition in HLM. In pharmacokinetic experiments, it was observed that after gavage administration of 48 mg/kg napabucasin and 20 mg/kg arbidol, napabucasin inhibited the metabolism of arbidol in vivo and significantly changed the pharmacokinetic parameters of arbidol, such as AUC(0-t) and AUC(0-∞), in rats. We also found that napabucasin increased the AUC(0-t) and AUC(0-∞) of M6-1, the main metabolite of arbidol. This study provides a reference for the combined use of napabucasin and arbidol in clinical practice.